Effect of probiotic, prebiotic, and synbiotic on the gut microbiota of autistic children using an in vitro gut microbiome model - Duque, Ana Luiza Rocha Faria [UNESP]; Demarqui, Fernanda Manaia [UNESP]; Santoni, Mariana Marchi [UNESP]; Zanelli, Cleslei Fernando [UNESP]; Adorno, Maria Angela Tallarico; Milenkovic, Dragan; Mesa, Victoria; Sivieri, Katia [UNESP] (Elsevier, 2021)
Imbalances in gut microbiota composition occur in individuals with autism spectrum disorder (ASD). The administration of probiotics, prebiotics, and synbiotics is emerging as a potential and promising strategy for regulating the gut microbiota and improving ASD-related symptoms. We first investigated the survival of the probiotics Limosilactobacillus (L.) reuteri and Bifidobacterium (B.) longum alone, mixed and combined with a galacto-oligosaccharide (GOS) under simulated gastrointestinal conditions. Next, we evaluated the impact of probiotics (L. reuteri + B. longum), prebiotic (GOS), and synbiotic (L. reuteri + B. longum + GOS) on gut microbiota composition and metabolism of children with ASD using an in vitro fermentation model (SHIME®). The combination of L. reuteri, B. longum, and GOS showed elevated gastrointestinal resistance. The probiotic, prebiotic, and synbiotic treatments resulted in a positive modulation of the gut microbiota and metabolic activity of children with ASD. More specifically, the probiotic treatment increased the relative abundance of Lactobacillus, while the prebiotic treatment increased the relative abundance of Bifidobacterium and decreased the relative abundance of Lachnoclostridium. Changes in microbial metabolism were associated with increased short-chain fatty acid concentrations and reduced ammonium levels, particularly in the prebiotic and synbiotic treatments.
Keywords: Autism spectrum disorder; Bifidobacterium longum; Galacto-oligosaccharide; Limosilactobacillus reuteri; Microbiota modulation; SHIME®